The Role of Artificial Intelligence (AI) in Mathematics Learning - Palupi Putri, Dini; Susanta, Agus; Sapri, Johannes (Corolla International Conference, 2024)
Mathematics learning facilitates the development of students' critical, creative, innovative, logical thinking and problem-solving skills. These abilities can be supported by AI, where AI is an artificial intelligence that can help lecturers and students in planning, implementing and understanding mathematics learning. In other words, learning mathematics with AI is able to produce students who are capable of receiving, analyzing, and applying information in accordance with the demands of the current digital era. This study aims to describe several roles of AI in the mathematics learning process. The research method used in this study is qualitative with the type of literature study. The results of the study show that the role of AI in mathematics learning includes: a. can check the answers to student problem solving; b. overcoming the use of notation, symbols and images in mathematics learning; c. facilitate a deeper understanding of mathematical materials; d. motivate students in the process of learning mathematics. The use of AI in mathematics learning in the current digital era needs to be recommended to develop mathematical abilities while still using relevant signs.